Tel1 is recruited at chromosomal loop/axis contact sites to modulate meiotic DNA double-strand breaks interference - Dorme, Marie; Luciano, Pierre; Cayrou, Christelle; Aithal, Rakesh; Vernerey, Julien; Borde, Valérie; Géli, Vincent; Llorente, Bertrand; Garcia, Valerie (PLOS Genetics, 2025)
Author summary During meiosis, a special type of cell division that produces gametes, cells intentionally break their own DNA at preferred genomic sites (hotspots) to help shuffle genetic material between chromosomes. The repair process of those breaks, called homologous recombination, is crucial for genetic diversity and for ensuring chromosomes are distributed correctly to gametes. The number and location of DNA breaks are tightly controlled to prevent errors that could affect genetic stability. In the yeast model S. cerevisiae, a protein called Tel1 (the counterpart of ATM in mammals, a DNA damage sensor) helps limit the number of breaks per cell. Our research shows that Tel1 is recruited to DNA breaks and to specific chromosome structures (called axis), supporting the idea that DNA breaks happen within the axis environment. We also found that recruitment of Tel1 to DNA breaks depends on another protein, Xrs2. This interaction is crucial to limit further DNA breaks formation and to arrest cell cycle progression in response to DNA breaks. Overall, these findings shed light on Tel1 dynamics on meiotic chromosomes, and reveal how Tel1 and Xrs2 work together to maintain genetic stability during meiosis, a process essential for healthy reproduction and evolution.